2010
DOI: 10.2353/ajpath.2010.090767
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Von Hippel-Lindau in Glomerular Podocytes Results in Glomerular Basement Membrane Thickening, Ectopic Subepithelial Deposition of Collagen α1α2α1(IV), Expression of Neuroglobin, and Proteinuria

Abstract: Vascular endothelial growth factor, which is critical for blood vessel formation, is regulated by hypoxia inducible transcription factors (HIFs). A component of the E3 ubiquitin ligase complex, von Hippel-Lindau (VHL) facilitates oxygen-dependent polyubiquitination and proteasomal degradation of HIF␣ subunits. Hypothesizing that deletion of podocyte VHL would result in HIF␣ hyperstabilization, we crossed podocin promoter-Cre transgenic mice, which express Cre recombinase in podocytes beginning at the capillary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 58 publications
(66 reference statements)
0
18
0
Order By: Relevance
“…For example, Vhlh inactivation in the podocytes resulted in fibrotic glomerular defects. 35,36 The Pepck-Cre-driven conditional knockout mice also developed fibrosis in 418-monthold mice after partial nephrectomy of one kidney and complete removal of the other. 37 Inactivation of Hif-1α in the proximal tubular epithelium was protective against unilateral ureteral obstruction-induced kidney injury.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Vhlh inactivation in the podocytes resulted in fibrotic glomerular defects. 35,36 The Pepck-Cre-driven conditional knockout mice also developed fibrosis in 418-monthold mice after partial nephrectomy of one kidney and complete removal of the other. 37 Inactivation of Hif-1α in the proximal tubular epithelium was protective against unilateral ureteral obstruction-induced kidney injury.…”
Section: Discussionmentioning
confidence: 97%
“…However, others have shown that deletion of von Hippel-Lindau protein, a HIF ubiquitin ligase, in podocytes promotes apoptosis and proteinuria. 54, 55 Podocyte-specific ND HIF-1α-expressing mice are reported to lack a disease phenotype, although only a low expression level could be achieved. 56 It is possible that we did not observe an effect of HIF-1α on proteinuria because direct podocyte damage by LMB2 bypasses any potential role for HIF-1α in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…After the stated perfusion times, blood samples were collected, and both kidneys were removed for mRNA, protein and histological analyses. Glomeruli were isolated by graded sieving as previously described [14].…”
Section: Animal Studiesmentioning
confidence: 99%